The Work of Political Armadores in Argentina: ‘Behind the Scenes’ Challenges, Instruments and Skills - Gené, Mariana (2018)
This article analyses the multi-faceted character of political work based on research on political operators or armadores from the return to democracy onward in Argentina. It analyses the role of the Ministry of Interior and the political functions it performed for a long time through political ministry of the national cabinet and the tools at its disposal in confronting the challenges of political brokerage. The work involved in political brokerage between actors undertaken by the Ministry from 1983 onward is also analysed with particular attention focused on the differences across historical periods and the resources and skills involved in this process.